Adaptive Governance In The Transformation Process Of Kintamani Tourism Attraction Management By Bangli District Government - Nandini. BG, Dev; Gorda, A.A. Ngurah Eddy Supriyadinata; Subanda, Nyoman; Gorda, A.A. Ngurah Oka Suryadinatha (UNIVERSITAS PAKUAN, 2023)
This research discusses the implementation of adaptive governance in the management of Kintamani tourist attraction (DTW) in Bangli Regency. Tourism is an important sector that can boost the economy, where Bali has been recognized as one of the world's best tourist destinations. The main problems found were the lack of collaboration between village officials and the sub-district head, as well as challenges in accessibility and inadequate infrastructure. In addition, the lack of tourism training and education to the community as well as the unoptimal use of technology in tourism promotion are significant obstacles. This research used descriptive qualitative methods with interviews and field observations to collect data. Proposed solutions include increased collaboration between the district government and village-level agencies to bridge communication and tourism management. In addition, improving accessibility and road infrastructure needs to be prioritized to support sustainable tourism growth. Tourism training and education for the community as well as optimizing the use of technology, including reactivating the Sadia Bangli application, are also suggested to improve tourism promotion and management. The results show that the current collaboration has involved academics, the private sector, and non-profit organizations, but still needs to be improved, especially in fully involving village officials and communities. The government's flexibility in adjusting to changes is evident in the increase in business licenses and efforts to protect agricultural land. However, accessibility issues and road infrastructure still require special attention. On the learning aspect, although there has been training, it has not been sufficient and equitable.